2010
DOI: 10.1111/j.1365-3156.2010.02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of tuberculosis in an Urban West African setting: is there evidence of clustering?

Abstract: Summaryobjectives To describe the pattern of tuberculosis (TB) occurrence in Greater Banjul, The Gambia with Geographical Information Systems (GIS) and Spatial Scan Statistics (SaTScan) and to determine whether there is significant TB case clustering. results Of 1145 recruited patients with TB, 84% were permanent residents with 88% living in 37 settlements that had complete maps available down to settlement level. Significant high-and low-rate spatial and space-time clusters were identified in two districts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 31 publications
2
51
0
8
Order By: Relevance
“…A countrywide study performed in Brazil between 2002 and 2009 found that clusters of high-rate municipalities were present in the Central-West Region along the Paraguayan border; in the North Region (Amazonas State); along the northeast coastline and on the south/southeast coast, around the metropolitan areas of Rio de Janeiro, São Paulo and Porto Alegre 9 . Others studies performed in Africa's countries, like Ethiopia and Gambia also found evidence of significant clustering of TB cases 30,42 .…”
Section: Discussionmentioning
confidence: 99%
“…A countrywide study performed in Brazil between 2002 and 2009 found that clusters of high-rate municipalities were present in the Central-West Region along the Paraguayan border; in the North Region (Amazonas State); along the northeast coastline and on the south/southeast coast, around the metropolitan areas of Rio de Janeiro, São Paulo and Porto Alegre 9 . Others studies performed in Africa's countries, like Ethiopia and Gambia also found evidence of significant clustering of TB cases 30,42 .…”
Section: Discussionmentioning
confidence: 99%
“…19 It is not certain whether or not the differences in incidence rates obtained using passive case detection are real: active case detection is necessary to resolve the issue. 20 It is highly likely that reduced access to diagnostic services in the outlying islands leads to underdiagnosis and low referral rates for sputum smears. 21 In settings using passive case detection, more TB cases are male than female; the male to female ratio is more evenly balanced when active case detection is used.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage to care remains challenging and will require creative interventions to impact morbidity [18]. And as TB is known to cluster in hyperendemic "hotspots" often characterized by crowding [16,19], HIV infection [20], and other social determinants [21], new approaches, such as mapping and spatial analysis, may be of value in contributing to basic elements of TB control [22].…”
Section: Introductionmentioning
confidence: 99%